Power and Voices of Authority in the Media Narrative of Malaysian Natives: Combining Corpus Linguistics and Discourse Analysis Approaches - Ismail, Habibah; Abd Majid, Siti Norzaimalina; Hazleena Baharun; Hazlina Abdullah (Penerbit Univ Kebangsaan Malaysia, 2024)
Indexed by Scopus/WOS